Enhancing Acclimatization Conditions for Vriesea splendens ‘Fire’: A Comparative Analysis of Substrate Effects on Growth and Survival - Eman Abdelhakim Eisa; Daniela Salome Pasquel Davila; Máté Ördögh (Plants)
This study investigates the acclimatization success of Vriesea splendens ’Fire’, a popular ornamental bromeliad, through in vitro propagation on various substrates. Due to the increasing demand for V. splendens, micropropagation offers a promising solution to overcome the limitations of traditional propagation methods. In this research, acclimatization was conducted in two trial types: in the one-step greenhouse conditions, and in two-step acclimatization, which introduced a controlled laboratory step before transferring plants to the greenhouse. The substrates examined included pure and mixed forms of turf, perlite, coco coir, pine bark (hereafter referred to as bark), moss, and vermiculite. Morphological traits such as plant height, leaf length, number and length of roots, and fresh weight were evaluated, together with physiological parameters, such as chlorophyll and carotenoid concentrations and survival percentage, to test the effectiveness of acclimatization. Coco coir-based substrates significantly enhanced plant height, root development, and survival percentages in both experiments compared with other substrates, thus proving its suitability for the propagation of V. splendens. Vermiculite had the highest survival rate during one-step acclimatization, whereas turf showed a very good performance in two-step acclimatization. On the opposite side, substrates containing bark and moss showed a reduced effect on plant growth and survival, which indicated the vital role of substrates for best development. Statistical analyses confirmed the superiority of some combinations of substrates related to physiological health, showing that optimal acclimatization results could be improved by a chosen substrate. These results strengthen the present in vitro propagation protocols of the Vriesea species by confirming the relevance of substrate choice in producing hardy plants with good commercial prospects.